Characterisation of a novel light activated adhesive scaffold: Potential for device attachment. (September 2016) - Ark, Morris; Boughton, Philip; Lauto, Antonio; Tran, Giang T.; Chen, Yongjuan; Cosman, Peter H.; Dunstan, Colin R.
Abstract: The most common methods for attaching a device to the internal tissues of the human body are via sutures, clips or staples. These attachment techniques require penetration and manipulation of the tissue. Tears and leaks can often be a complication post-attachment, and scarring usually occurs around the attachment sites. To resolve these issues, it is proposed to develop a soft tissue scaffold impregnated with Rose Bengal/Chitosan solution (RBC-scaffold, 0.01% w/v Rose Bengal, 1.7% w/v Medium Molecular Weight Chitosan). This scaffold will initially attach to the tissue via a light activation method. The light activates the dye in the scaffold which causes cross-links to form between the scaffold and tissue, thus adhering them together. This is done without mechanically manipulating the surrounding tissue, thus avoiding the issues associated with current techniques. Eventually, the scaffold will be resorbed and tissue will integrate for long-term attachment. A variety of tests were performed to characterise the RBC-scaffold. Porosity, interconnectivity, and mechanical strength were measured. Light activation was performed with a broad spectrum (380–780 nm) 10 W LED lamp exposed to various time lengths (2–15 min, Fluence range 0.4–3 J/cm 2 ). Adhesive strength of the light-activated bond was measured with lap-shear tests performed on porcine stomach tissue. Cell culture viability was also assessed to confirm tissue integration potential. These properties were compared to Variotis™, an aliphatic polyester soft tissue scaffold which has proven to be viable for soft tissue regeneration. The RBC-scaffolds were found to have high porosity (86.46±2.95%) and connectivity, showing rapid fluid movement. The elastic modulus of the RBC-scaffolds (3.55±1.28 MPa) was found to be significantly higher than the controls (0.15±0.058 MPa, p <0.01) and approached reported values for human gastrointestinal tissue (2.3 MPa). The maximum adhesion strength achieved of the RBC-scaffolds was 8.61±2.81 kPa after 15 min of light activation, this is comparable to the adhesion strength of fibrin glue on scaffolds. Cell attachment was seen to be similar to the controls, but cells appeared to have better cell survivability. In conclusion, the RBC-scaffolds show promise for use as a novel light activated attachment device with potential applications in attaching an anti-reflux valve in the lower oesophagus and also in wound healing applications for stomach ulcers. Graphical abstract: Highlights: Light-activated Adhesive Scaffold successfully developed. Achieved adhesive strength between soft tissue and scaffold of 8.61 ± 2.81 kPa. Scaffold has properties conducive for tissue integration. The potential for use in device attachment is high.